Ogilvie’s Syndrome after Cesarean Section: Case Report in Saudi Arabia and Management Approach - Lamiaa Elsebay; Mariam Ahmed Galal (Case Reports in Obstetrics and Gynecology)
Background. Acute colonic pseudoobstruction or Ogilvie’s syndrome is a rare entity that is characterized by acute dilatation of the colon without any mechanical obstruction. It is usually associated with medical disease or surgery and rarely occurs spontaneously. If not diagnosed early, Ogilvie’s syndrome may cause bowel ischemia and perforation. Case. A G7P4+2, 40-year-old woman, who is a known case of gestational diabetes mellitus during her current pregnancy, four previous cesarean sections, two early pregnancy losses at six-week gestation, and hypothyroidism, underwent uncomplicated elective cesarean section, after which she complained of abdominal distention. Conclusion. Ogilvie’s syndrome is a rare condition yet of interest to obstetricians, midwifery staff, and general surgeons because its early diagnosis and prompt treatment are the keystones to avoid any subsequent fatal complications. This case report reviews the clinical characteristics, diagnostic methods, and management of Ogilvie’s syndrome. Moreover, we suggest a management approach to help in early diagnosis and prompt management to improve the outcome of this potentially serious condition.